Mini-India: the politics of migration and subalternity in the Andaman Islands - Zehmisch, Philipp (Oxford University Press, 2017)
This text fills a gap in the under-represented scholarship on the migrant and settler society of the Andaman Islands. The study focuses on how marginalised people from criminalised, low-class, low-caste, landless, refugee, repatriated, and Adivasi backgrounds have come to form a cosmopolitan, overseas conglomerate of communities - a Mini-India that incorporates the cultural, religious, social, ethnic, and class diversity of the subcontinent
This edition previously issued in print: 2017
Includes bibliographical references and index
Zielgruppe - Audience: Specialized
Keywords: Andaman Islands (India) -- Ethnic relations; Andaman Islands (India) -- Emigration and immigration; Electronic book; Ethnologie; Inder; Einwanderung; Andamanen